The effect of caffeine supplementation on exercise performance evaluated by a novel animal model - da Silva, Roberto Pacheco; Martinez, Denis; Fiori, Cintia Zappe; Bueno, Kelly Silveira da Silva; Ramos, Jhoana Mercedes Uribe; Kaminski, Renata Schenkel; Fischer, Marcia Kraide; Silva, Leticia Maria Tedesco; Giordani, Juliana Neves; Brendler, Juliana Heitich; et al. (Clinical and Biomedical Research, 2017)
Introduction: Caffeinated drinks are used for improve performance. Animal models represent investigational strategy that circumvents most of the drawbacks of research in humans, including motivational factors and the placebo effect. No animal model that could test whether different forms of administering caffeine affect exercise propensity was found in the literature. Methods: An animal model of grouped voluntary exercise was tested. Two-month-old male C57/bl mice were housed in a cage fitted with one running wheel and a monitoring system. Six animals per cage were introduced individually. To assess the sensitivity of the model, the effect of different caffeinated drinks was observed in mice exercising ad libitum. During 2 days, the mice received: 1) pure anhydrous caffeine 0.125 mg/mL (PC), 2) cola drink (CC), and 3) caffeine-taurine-glucuronolactone drink (CTG), intercalating wash-out periods of 2 days, receiving pure water. Results: The distance run during the periods of water ingestion was significantly lower than during the periods of stimulant drinks ingestion: PC (5.6±1.3 km; p = 0.02), of CC ingestion (7.6±0.6 km; p = 0.001), and of CTG ingestion (8.3±1.6 km; p = 0.009). The performances when ingesting the three caffeinated drinks do not follow a dose-response curve. Conclusions: The model described here was able to measure the effect of caffeine intake on voluntary exercise of mice. The sensitivity of the model to the effect of caffeine needs to be further validated. The action of each component of the drinks on exercise performance needs to be clarified in future research. The present model is adequate for such investigation. Key words: Exercise; caffeine; energy drinks; running